A kind of black near-infrared transparent glass and preparation method thereof
The black near-infrared glass prepared through chemical reinforcement process solves the problems of low transmittance and insufficient hardness in the infrared segment, and achieves a combination of high transmittance and high hardness, which is suitable for high-demand applications such as lidar.
Patent Information
- Application Number
- CN202411977972.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing infrared transmittance glass is difficult to reach more than 80% in the infrared segment, it has high cost and low hardness, poor wear and scratch resistance, and has certain disadvantages for lidar use.
A black near-infrared glass is prepared by chemical reinforcement technology, which consists of SiO2, Al2O3, Na2O, K2O, ZrO2, ZnO and Sb-containing compounds, and has high light transmittance and high hardness properties.
It has achieved high light transmittance in the near infrared segment (780-2000 nm) and basically impermeable in the visible light area, and has high hardness, scratch resistance and excellent chemical resistance.
Smart Images

Figure CN119774872A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical glass, and in particular to a black near-infrared transparent glass and a preparation method thereof. Background Art
[0002] With the continuous advancement of modern technology, LiDAR (Light Detection and Ranging) has become an indispensable sensing technology in many fields. From self-driving cars to drone mapping, from industrial detection to environmental monitoring, LiDAR provides reliable data support for various application scenarios with its high precision and long-distance measurement capabilities. However, to achieve the efficient operation of LiDAR, the selection of key components is crucial, especially infrared-transmitting glass plays a vital role. Infrared-transmitting glass is an optical material with high transmittance, low absorption rate and excellent environmental resistance, which is widely used in the windows and lens parts of LiDAR. These glass materials can not only effectively protect the internal optical components from interference from the external environment, but also ensure the efficient transmission of laser signals in a specific infrared band.
[0003] At present, the traditional infrared-transmitting glass used is either chalcogenide glass or ordinary glass coating. The former is difficult to achieve an infrared transmittance of more than 80%, while the latter is expensive. Their common disadvantages are low hardness, poor wear resistance and scratch resistance, which have certain drawbacks when used in LiDAR. Summary of the invention
[0004] The purpose of the present application is to provide a black near-infrared transparent glass, the product glass is black and evenly colored, has extremely high light transmittance in the near-infrared range (780-2000nm), and basically has no light transmittance in the visible light region (400-700nm); at the same time, the product glass has high strength performance, high hardness, scratch resistance and other capabilities, and has excellent quality.
[0005] Another object of the present application is to provide a method for preparing the above-mentioned black near-infrared transparent glass, which obtains a product glass with high strength performance through chemical strengthening. The product quality is excellent, the process operation is simple, and it is conducive to large-scale production and application.
[0006] The technical solution of this application is as follows:
[0007] On the one hand, the embodiment of the present application provides a black near-infrared transparent glass, which is prepared from raw materials including the following components by mass percentage:
[0008] SiO 2 :58~68%,Al 2 O 3 :2~5%,Na 2 O: 10-20%, K2 O: 5-10%, ZrO 2 : 0.5~4%, ZnO: 4~10%, Sb compounds: 1~5%.
[0009] Among them, SiO 2 It is the main component that forms silicon-oxygen tetrahedrons and connects to form the glass network structure, and is the basic skeleton of glass. 2 The addition amount is 58-68%, preferably 60-65%. 2 When SiO is less than 58%, the chemical stability of the glass is poor and the expansion coefficient increases, thereby reducing the mechanical strength of the glass. 2 When it is >68%, the high temperature viscosity of the glass increases, melting becomes difficult and the color development reaction of the glass is inhibited, so its content needs to be controlled within an appropriate range.
[0010] Al 2 O 3 It is easy to form tetrahedral coordination, [AlO 4 ] tetrahedral coordination can help [SiO 4 ]tetrahedrons together build a tighter network and are an important component of the glass network structure. [AlO 4 ] Tetrahedron can also significantly enhance the ion exchange process during chemical strengthening, but while making the structure more compact, it will also reduce the coloring ability and reduce the cutoff performance of the glass; after comprehensive consideration, the Al 2 O 3 The addition amount is 2-5%, preferably 2-4%.
[0011] Na 2 O and K 2 O is a good co-solvent in glass components and an important element for ion exchange in chemical strengthening. It can enhance the scratch resistance of glass through ion exchange in chemical strengthening. The introduction of alkali metal oxides can reduce the melting temperature of glass. At high temperatures, alkali metals and sulfur form non-volatile sulfides, which stabilize sulfur. 2 O and K 2 O can reduce the viscosity of the glass, make the glass longer, and facilitate the formation of crystal nuclei during the cooling process, making the glass easier to color; however, the introduction of a large amount of alkali metals will inevitably cause a certain loss in the chemical resistance and strength of the glass. 2 The amount of O added is 10-20%, preferably 12-17%; K 2 The amount of O added is 5-10%, preferably 6-9%.
[0012] ZrO 2It is not only resistant to water and acid, but also highly resistant to alkali; an appropriate amount of ZrO 2 It helps to improve the chemical durability and hardness of glass; however, if it contains too much ZrO 2 On the one hand, the glass's resistance to devitrification is reduced, and on the other hand, its melting property is poor and there is a tendency to devitrification, which makes glass molding difficult. 2 The dosage range is 0.5-4%, preferably 1-3%.
[0013] ZnO in glass can improve the chemical stability of glass, reduce the high temperature viscosity of glass, and can 2 With the cooperation of ZnO, the volatilization of coloring substances is reduced during the melting stage, and the cut-off performance of the glass is improved. If the ZnO content is lower than 4%, the cut-off performance of the glass cannot meet the requirements, and the chemical stability of the glass is reduced. Therefore, in the present application, the lower limit of the ZnO content is 4%. If the ZnO content exceeds 10%, the structural transformation of the coloring substances is promoted, which will greatly increase the visible light transmittance of the glass, making it difficult to melt black glass. Therefore, the upper limit of the ZnO content in the present application is 10%.
[0014] Sb-containing compounds (such as Sb 2 O 3 , Sb 2 O 5 , Sb 2 S 3 The color of the glass is related to the number of antimony sulfide colloid particles. The more the number, the darker the color. Therefore, the content of Sb-containing compounds and S should be within an appropriate range. After comprehensive consideration, the Sb-containing compounds (such as Sb 2 O 3 , Sb 2 O 5 , Sb 2 S 3 The content of sulfur in the present application refers to the content of sulfur in all sulfur-containing substances in the glass converted into elemental sulfur. In the present application, S can be introduced in the form of elemental sulfur and / or sulfur-containing compounds.
[0015] Furthermore, in some embodiments of the present application, the Sb-containing compound is Sb 2 O 3 , Sb 2 O 5 , Sb2 S 3 Any one or more of .
[0016] Further, in some embodiments of the present application, the above-mentioned glass has a light transmittance of ≥88% in the 780-2000nm band, and a cut-off wavelength of >650nm;
[0017] The light transmittance of the above glass in the wavelength range of 400-700 nm is 0%.
[0018] Furthermore, in some embodiments of the present application, the above raw materials further include the following components by mass percentage:
[0019] CaO: 0-5%, TeO 2 :0~3%,Co 3 O 4 :0~0.1%,Cu 2 O: 0~0.1%, S powder: 0~2%.
[0020] Among them, CaO is an optional component of the glass in the present application. Ca can significantly reduce the melting temperature of glass, play a role in reducing the melting temperature of glass, and can indirectly reduce the volatilization of components constituting the color development structure in the glass. However, the contribution of Ca to the hardness of glass is relatively low, and it is not conducive to improving the strength of glass by chemical strengthening methods. Taking all factors into consideration, the content range of Ca in the present application is 0-5%, preferably 0-4%, and more preferably 0-2%.
[0021] TeO 2 It is an optional component in the glass formula of this application. It is based on TeO in the glass structure. 4 It is mainly tetrahedral. When the alkaline earth metal content increases further, it will transform into TeO 3 In the form of a triangular pyramid, it will increase the refractive index of the glass, making the emission cross section of the glass larger. This property can improve the spectral characteristics of the glass and thus increase the transmittance in the near-infrared band.
[0022] Co 3 O 4 It is an optional component in the glass formula of this application. It only plays a role in absorbing visible light and is beneficial to the production of black glass. After comprehensive consideration, Co in this application 3 O 4 The content should be controlled at 0-0.1%.
[0023] Cu 2 Cu is an optional component in the glass formula of the present application. The color structure of the glass in the present application is dispersed in the glass, and there may be a problem of insufficient light absorption near the cutoff limit. In the case of glass melting in the present application, the Cu component is generally Cu +exists in the form of Cu + It can enhance the light absorption near the glass cutoff limit. However, Cu + Too high a content may result in a decrease in the transmittance of the glass of the present application product in the 1000-1500nm band. 2 The O content should be controlled between 0 and 0.1%.
[0024] In the present application, S powder is mainly used to match Sb-containing compounds. The relevant effects have been described above and will not be repeated here.
[0025] Furthermore, in some embodiments of the present application, the above-mentioned raw materials further include C powder whose mass is 0 to 2% of the total mass of the above-mentioned raw materials.
[0026] In the present application, the glass melting needs to be carried out in a reducing atmosphere, so a certain amount of carbon powder needs to be added depending on the situation, and the carbon powder also has the effect of increasing the color, which is conducive to the preparation of black glass. In the present application, the appropriate amount of C powder added is 0-2%.
[0027] Furthermore, in some embodiments of the present application, in the above raw materials, 3.5≤(mass of Sb-containing compound+mass of S powder) / mass of C powder≤5.0.
[0028] In the present application, in order to obtain a higher near-infrared transmittance, it is necessary to satisfy 3.5≤(mass of Sb-containing compound+mass of S powder) / mass of C powder≤5.0.
[0029] Furthermore, in some embodiments of the present application, among the above raw materials, ZnO, Sb compound, and TeO 2 The total mass of the raw materials is ≥ 6% of the total mass of the raw materials.
[0030] In the present application, in order to improve the transmittance of the glass in the near-infrared region, it is necessary to control the composition of ZnO, Sb-containing compounds and TeO 2 Dosage.
[0031] Further, in some embodiments of the present application, among the above raw materials, (SiO 2 Quality+Al 2 O 3 mass) / (Na 2 O quality + K 2 O quality)<3.0.
[0032] In this application, in order to obtain higher glass hardness and stable chemical properties, it is necessary to control the SiO 2 、Al 2 O 3 and R 2 The matching relationship of O.
[0033] On the other hand, the embodiment of the present application further provides a method for preparing the above-mentioned black near-infrared transparent glass, which comprises the following steps:
[0034] S1: preparing various component materials in the raw material in proportion, mixing and melting them, and processing them to obtain basic glass;
[0035] S2: Perform color development on the base glass, and then process it according to the required size specifications to obtain a semi-finished product;
[0036] S3: Chemically strengthen the semi-finished product to obtain finished glass.
[0037] Furthermore, in some embodiments of the present application, in the above step S1, the melting temperature is 1450-1560°C.
[0038] Furthermore, in some embodiments of the present application, in the above step S2, the color development treatment is carried out at Tg±10°C, and the color development treatment time is 4 to 24 hours, preferably 4 to 16 hours.
[0039] Furthermore, in some embodiments of the present application, in the above step S3, molten potassium nitrate is used to immerse the semi-finished product at 380-430° C., preferably 390-410° C., for chemical strengthening, and the strengthening time is 3-7 hours, preferably 4-6 hours.
[0040] Furthermore, in some embodiments of the present application, in the above step S1, after the component materials are mixed and melted, they are sequentially clarified and homogenized, formed, and annealed to obtain the basic glass.
[0041] Furthermore, in some embodiments of the present application, in the above step S1, the process method for preparing the basic glass is any one of the conventional glass preparation processes such as ingot casting, float method, overflow method, down-draw method, etc.
[0042] Furthermore, in some embodiments of the present application, in the above step S2, cutting, CNC, grinding, polishing and other processing are performed according to the required size specifications to obtain a semi-finished product.
[0043] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0044] In view of the above aspects, the embodiments of the present application provide a black near-infrared transparent glass and a preparation method thereof, wherein the glass product has a uniform and stable color, is not easily discolored by the increase of pH or temperature, and has a simple production process. The transmittance is high in the near-infrared range (780-2000nm), and the cut-off wavelength is greater than 650nm; and it has basically no light transmission ability in the visible light region (400-700nm).
[0045] During its preparation process, chemical strengthening is carried out to make the Vickers hardness of the product glass at least greater than 600MPa, the ultimate scratch resistance can bear a load of more than 2.5kg, the scratch width with a load of 1.0kg is ≤80μm and there is no edge collapse; at the same time, the product glass has excellent chemical resistance, with water resistance level HGB2, acid resistance level S2, and alkali resistance level A2. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 This is a light transmittance curve of the glass product of Example 1 of the present application in the wavelength range of 200 to 1500 nm;
[0048] Figure 2 This is a physical photo of the glass product of Example 1 of the present application;
[0049] Figure 3 This is a physical photo of the glass product of Comparative Example 1 of this application;
[0050] Figure 4 This is a physical photo of the glass product of Comparative Example 2 of this application. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0052] It should be noted that the term "include" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.
[0053] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0054] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0055] Example
[0056] This embodiment provides a black near-infrared transparent glass, which is prepared by the following steps:
[0057] S1: Prepare the various components of the raw materials in proportion, mix them, and then melt, clarify, shape and anneal to obtain a glass ingot (i.e., basic glass) of 120*120*40mm;
[0058] S2: The base glass is subjected to color development treatment in a muffle furnace, and then after cutting, grinding and polishing, a semi-finished glass sheet with a specification of 50*50*5mm is obtained.
[0059] S3: Using molten KNO 3 The semi-finished glass pieces are immersed for chemical strengthening to obtain finished glass.
[0060] The specific raw material group distribution ratios of various embodiments are shown in Table 1:
[0061] Table 1
[0062]
[0063]
[0064] In the preparation methods of each embodiment, the condition parameters of the color development treatment in step S2 are shown in Table 2:
[0065] Table 2
[0066]
[0067] In the preparation methods of each embodiment, the relevant condition parameters of chemical strengthening in step S3 are shown in Table 3:
[0068] Table 3
[0069]
[0070] Test example
[0071] The glass products obtained in each embodiment were tested for performance:
[0072] The test method for the spectral performance of black near-infrared transparent glass is to use an ultraviolet-visible spectrophotometer to test the spectrum of the glass sample, and the test wavelength range is 200 to 1500nm.
[0073] The following defined parameters are used to characterize the spectral characteristics of the black near-infrared transparent glass in the present application.
[0074] The cut-off wavelength is defined as the wavelength corresponding to 5% transmittance, in nm.
[0075] The Vickers hardness of black near-infrared transparent glass was measured by using a microhardness tester with reference to standard GB / T37900-2019;
[0076] The scratch resistance of black near-infrared transparent glass is measured by using a scratch resistance tester with reference to standard ISO12137-2:1997, wherein the scratch width at a load of 1 kg is measured by observation under a polarizing microscope, and the ultimate scratch resistance load refers to the load value when the glass is scratched by loading a load until the glass breaks.
[0077] The chemical stability of black NIR-transmitting glass is determined according to DIN 12116, ISO 695 and ISO 719 standards.
[0078] Specifically, the DIN 12116 standard is a measure of the resistance of glass to decomposition when placed in an acidic solution. In simple terms, the DIN 12116 standard uses a weighed sample of polished glass with a known surface area and then exposes the glass sample to a proportional amount of boiling 6Mol / L hydrochloric acid for 6 hours. The sample is then removed from the solution, dried and weighed again. The mass loss of the glass when exposed to the acid solution is a measure of the acid durability of the sample, with smaller values indicating greater durability. The test results are recorded in units of mass per surface area, specifically mg / dm 2 The DIN 12116 standard is divided into four independent grades. S1 grade refers to weight loss up to 0.7 mg / dm 2 ; S2 level refers to weight loss from 0.7mg / dm 2 To 1.5mg / dm 2 ; S3 level refers to weight loss from 1.5mg / dm 2 To 15mg / dm 2 ; and S4 level means weight loss greater than 15 mg / dm 2 .
[0079] The ISO 695 standard is a measurement of the mass loss per unit area when glass is placed in an alkaline solution. Specifically, the ISO 695 standard uses a weighed polished glass sample and places the glass sample in a boiling 1Mol / L NaOH+0.5Mol / LNa 2 CO 3 The sample is then removed from the solution, dried and weighed again. The mass loss of the glass in the alkaline solution is a measure of the sample's resistance to alkali, with smaller values indicating greater resistance to alkali. Similar to the DIN 12116 standard, the results of the ISO 695 standard are recorded in units of mass per surface area, specifically mg / dm 2The ISO 695 standard is divided into three levels. Level A1 refers to a weight loss of up to 75 mg / dm 2 ; A2 level refers to weight loss from 75mg / dm 2 To 175mg / dm 2 ; and A3 refers to weight loss greater than 175mg / dm 2 .
[0080] ISO 719 standard is the glass in pure, CO2-free 2 The ISO 719 standard protocol uses crushed glass grains and mixes them with pure, CO2-free water at a temperature of 98°C and 1 atmosphere. 2 The solution was then titrated colorimetrically with dilute HCl to neutralize the pH. The amount of HCl required to titrate the solution to a neutral solution was then converted into an equivalent amount of Na 2 O, and precipitated Na per gram of glass 2 The smaller the value, the greater the water resistance. ISO 719 standard is divided into five levels. HGB1 type refers to the extracted equivalent Na 2 O up to 31μg; HGB2 type refers to the extracted equivalent Na 2 O is greater than 31 μg and up to 62 μg; HGB3 type refers to the extracted equivalent Na 2 O is greater than 62μg and up to 264μg; HGB4 type refers to the extracted equivalent Na 2 O is greater than 264 μg and up to 620 μg; HGB5 type refers to the extracted equivalent Na 2 O is greater than 620 μg and up to 1085 μg.
[0081] The light transmittance of the glass product of Example 1 in the wavelength range of 200 to 1500 nm was tested. Figure 1 shown.
[0082] The actual photo of the glass product of Example 1 is as follows Figure 2 shown.
[0083] The performance test results of the glass products of various embodiments are shown in Table 4:
[0084] Table 4
[0085]
[0086] Comparative Example
[0087] Based on the preparation method in the embodiment, the raw material ratio and related preparation process conditions were changed to obtain comparative examples 1 to 4, and the specific raw material ratios are shown in Table 5:
[0088] Table 5
[0089]
[0090]
[0091] In each comparative example preparation method, the relevant process condition parameters are shown in Table 6:
[0092] Table 6
[0093]
[0094] The performance of the glass obtained in each comparative example was tested, and the results were as follows:
[0095] Comparative Example 1 increases the ZnO content, while Comparative Example 3 does not add C powder. After the glass ingots are melted, no matter how long the color development time is extended, the glass does not develop color and always remains transparent; among them, the actual photos of the comparative product glass are as follows Figure 3 shown.
[0096] Comparative Example 2 increases the amount of Sb compounds, and the glass after melting loses transparency and presents colorful colors. The actual photo of the product glass is as follows: Figure 4 shown.
[0097] After strengthening, the glass sheet prepared in Comparative Example 4 has a scratch width of 158 μm under a load of 1 kg, a Vickers hardness of 450 MPa, a water resistance level of HGB4, and an acid resistance level of S3, which are not as good as the effects obtained by the products of the examples of the present application.
[0098] In summary, the embodiments of the present application provide a black near-infrared transparent glass and a preparation method thereof, wherein the color of the glass product is uniform and stable, and it will not be easily discolored by the increase of pH or temperature, and the production process is simple. The transmittance is high in the near-infrared section (780-2000nm), and the cut-off wavelength is greater than 650nm; it basically has no light transmittance in the visible light region (400-700nm). In its preparation process, by chemical strengthening, the Vickers hardness of the product glass can be at least greater than 600MPa, the extreme scratch resistance can load more than 2.5kg, the scratch width of 1.0kg load is ≤80μm and there is no edge collapse; at the same time, the product glass has excellent chemical resistance, water resistance level HGB2, acid resistance level S2, and alkali resistance level A2.
[0099] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A black near-infrared transparent glass, characterized in that: The invention is prepared from raw materials including the following components by mass percentage: SiO2: 58-68%, Al2O3: 2-5%, Na2O: 10-20%, K2O: 5-10%, ZrO2: 0.5-4%, ZnO: 4-10%, Sb compounds: 1-5%.
2. The black near-infrared transparent glass according to claim 1, characterized in that: The glass has a light transmittance of ≥88% in the 780-2000nm band and a cut-off wavelength of >650nm; The light transmittance of the glass in the wavelength range of 400-700 nm is 0%.
3. The black near-infrared transparent glass according to claim 1, characterized in that: The raw material also includes the following components by mass percentage: CaO: 0~5%, TeO2: 0~3%, Co3O4: 0~0.1%, Cu2O: 0~0.1%, S powder: 0~2%.
4. The black near-infrared transparent glass according to claim 3, characterized in that: The raw materials also include C powder whose mass is 0 to 2% of the total mass of the raw materials.
5. The black near-infrared transparent glass according to claim 4, characterized in that: In the raw materials, 3.5≤(mass of Sb-containing compound+mass of S powder) / mass of C powder≤5.
0.
6. The black near-infrared transparent glass according to claim 3, characterized in that: In the raw materials, the total mass of ZnO, Sb compound, and TeO2 is ≥ 6% of the total mass of the raw materials.
7. The black near-infrared transparent glass according to claim 1, characterized in that: In the raw materials, (mass of SiO2+mass of Al2O3) / (mass of Na2O+mass of K2O) is less than 3.
0.
8. A method for preparing the black near-infrared transparent glass according to any one of claims 1 to 7, characterized in that: It includes the following steps: S1: preparing various component materials in the raw material in proportion, mixing and melting them, and processing them to obtain basic glass; S2: Perform color development on the base glass, and then process it according to the required size specifications to obtain a semi-finished product; S3: Chemically strengthen the semi-finished product to obtain finished glass.
9. The method for preparing black near-infrared transparent glass according to claim 8, characterized in that: In the step S2, the color development treatment is carried out at Tg±10°C for 4 to 24 hours, preferably 4 to 16 hours.
10. The method for preparing black near-infrared transparent glass according to claim 8, characterized in that: In the step S3, molten potassium nitrate is used to immerse the semi-finished product at 380-430° C. for chemical strengthening, and the strengthening time is 3-7 hours.